Coherent X-ray radiation by relativistic electron in a structure “amorphous layer - periodic layered medium” - Blazhevich, S.V.; Drygina, Yu.A.; Nemtsev, S.N.; Noskov, A.V. (Вопросы атомной науки и техники, 2016)
The dynamic theory of coherent X-ray radiation by relativistic electron crossing a two-layer structure consisting
of an amorphous layer and a layer with artificial periodic structure has been developed. The process of radiation and
propagation of X-ray waves in an artificial periodic structure has been considered based on two-wave approximation
of dynamic diffraction theory in Laue scattering geometry. Развита динамическая теория когерентного рентгеновского излучения релятивистского электрона, пересекающего
двухслойную структуру, состоящую из аморфного слоя и слоя из искусственной периодической структуры. Процесс
излучения и распространения рентгеновских волн в искусственной периодической структуре рассмотрен на основе
двухволнового приближения динамической теории дифракции в геометрии рассеяния Лауэ. Розвинена динамічна теорія когерентного рентгенівського випромінювання релятивістського електрона, що перетинає двошарову структуру, що складається з аморфного шару і шару зі штучної періодичної структури. Процес випромінювання і поширення рентгенівських хвиль у штучній періодичній структурі розглянуто на основі двохвильового наближення динамічної теорії дифракції в геометрії розсіяння Лауе.